SYNERGETIC MODEL OF INTEGRATIVE AND ACTIVITY EDUCATIONAL SYSTEM AS A BASIS FORMING PLANETARY THINKING IN THE FUTURE AVIAFAHIVTSIV DURING TRAINING - Лузік, Е. В.; Тепнадзе, С. А. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2013)
The article investigates the theoretical and methodological aspects of mastering the synergetic model of integrative management and activity of the educational process in the technical colleges in the training of aviation specialists